2017
DOI: 10.1088/1475-7516/2017/01/035
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic of Horndeski theories

Abstract: We study the effects of Horndeski models of dark energy on the observables of the large-scale structure in the late time universe. A novel classification into Late dark energy, Early dark energy and Early modified gravity scenarios is proposed, according to whether such models predict deviations from the standard paradigm persistent at early time in the matter domination epoch. We discuss the physical imprints left by each specific class of models on the effective Newton constant µ, the gravitational slip para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 131 publications
(219 reference statements)
4
40
1
Order By: Relevance
“…The validity of the conjecture at all times is in tension with the previous work where the sign agreement is lost for z < 1.5 [167]. The reasons stems from how viable are the models considered: using only stability conditions (ghost and gradient) leads to the violation of the conjecture at small redshifts [167], while requiring additional priors based on observational constraints allows for the conjecture to be restored [155]. In particular, Solar System bounds on the variation of the Newton's constant translate into a stringent prior on f at present time [168].…”
Section: Phenomenology From µ σ and ηcontrasting
confidence: 55%
See 4 more Smart Citations
“…The validity of the conjecture at all times is in tension with the previous work where the sign agreement is lost for z < 1.5 [167]. The reasons stems from how viable are the models considered: using only stability conditions (ghost and gradient) leads to the violation of the conjecture at small redshifts [167], while requiring additional priors based on observational constraints allows for the conjecture to be restored [155]. In particular, Solar System bounds on the variation of the Newton's constant translate into a stringent prior on f at present time [168].…”
Section: Phenomenology From µ σ and ηcontrasting
confidence: 55%
“…The results showed that the conjecture holds very well within the QS approximation, but the exact behaviors of µ and Σ obtained with EFTCAMB violate the conjecture at k = 0.001 h/Mpc, where the full dynamics of the Horndeski models allows Σ > 1 and µ < 1 [131]. The validity of the conjecture at all times is in tension with the previous work where the sign agreement is lost for z < 1.5 [167]. The reasons stems from how viable are the models considered: using only stability conditions (ghost and gradient) leads to the violation of the conjecture at small redshifts [167], while requiring additional priors based on observational constraints allows for the conjecture to be restored [155].…”
Section: Phenomenology From µ σ and ηmentioning
confidence: 53%
See 3 more Smart Citations